Speechless. The complete third season [videorecording (DVD)] - Mascena, Megan; Driver, Minnie; Bowie, John Ross, 1971-; Yarbrough, Cedric, 1973- (Twentieth Century Fox Television, 2019)
Maya is the mom who will do anything for her husband, Jimmy, and kids Ray, Dylan, and JJ, her eldest son with cerebral palsy. This begins of this amusing and often unexpected comedy, the family, along with JJ's, aide Kenneth, head to London to meet up with Maya's long-estranged father, Martin, to ask him to help them in their time of need.